P23 Predicted risk of end-stage liver disease utilizing the UK-PBC risk score with continued standard of care and subsequent addition of OCA for 60 months in patients with PBC. (28th September 2020) - Mells, George; Jones, Dave; Digpal, Kuldip
Abstract : The UK-PBC Study group validated a long-term prognostic model of primary biliary cholangitis (PBC) that identified independent predictors of end-stage liver disease (ESLD). POISE was a randomized, double-blind (DB), placebo-controlled 12-month Phase 3 trial investigating obeticholic acid (OCA) treatment of PBC; a 5-year open-label extension (OLE) followed. We assessed the change in predicted risk of ESLD with the UK-PBC model in placebo patients (DB phase) who transitioned to OCA (OLE). POISE inclusion criteria: PBC diagnosis, alkaline phosphatase ≥1.67x upper limit of normal (ULN) and/or total bilirubin >ULN to <2x ULN, stable ursodeoxycholic acid (UDCA) dose or intolerant to UDCA. 73 patients were randomized to placebo; 66 enrolled in the OLE. Baseline, DB month 12, and OLE data through 60 months of OCA treatment were included in the UK-PBC algorithm to assess predicted risk of ESLD at 5, 10, and 15 years. The median age at baseline in the placebo group was 55 years; 93% were female, and 93% received daily UDCA (median dose, 15 mg/kg). After 1 year of standard-of-care (SOC), placebo patients demonstrated a slight increase in predicted risk of ESLD (table 1 ). After 1 year of OCA, predicted risk of ESLD at 5, 10, and 15 years was reduced to below baseline levels; these were sustained through the 60-month OLE. In POISE, the UK-PBC risk score predicted an increased risk of ESLD in PBC patients treated with SOC and placebo for 12 months. OCA treatment led to sustained reductions in predicted risk of ESLD through 60 months.